Nanostructural Hybrid Sensitizers for Photodynamic Therapy - Kepczynski, Mariusz; Dzieciuch, Monika; Nowakowska, Maria (Current Pharmaceutical Design, 2012)
Photodynamic therapy (PDT) is a clinically approved method for treatment of cancer, microbial infections, and some other diseases. PDT has proved effective in the treatment of malignancies of various organs, including lung, bladder, gastrointestinal tract, and skin, and in the therapy of bacterial infection of skin wounds and carious lesions. It employs a combination of light and a drug (photosensitizer, PS) to induce phototoxicity against cancerous cells or bacteria. The efficiency of currently used PSs is limited due to their hydrophobic nature, which causes aggregation of the PS in aqueous media and low tumor selectivity (a low value of the tumor-to-normal tissue ratio). The purpose of this review is to present some aspects of the current state of knowledge on nanostructural carriers for the PS delivery. In this paper we reviewed studies on the development of nanostructural materials for PDT, especially those based on the polymeric and liposomal formulation of PS. We focused mainly on the nanostructural PSs obtained by the covalent attachment of hydrophilic polymer chain to the low-molecular-weight PS, the incorporation of PS into polymeric nanostructures such as micelles, and the solubilization of PS in liposome carriers.
Keywords: liposomes